Investigation of natural fibre metal laminate as car front hood - Dhar Malingam, Sivakumar; Mohd Ishak, Noordiana; Mansor, Muhd Ridzuan; Razali, Nadlene; Mustafa, Zaleha; Ab Ghani, Ahmad Fuad (IOP Publishing Ltd., 2021)
Due to the increasing awareness on environmental impact and the needs towards sustainability, weight reduction of the vehicles is one of the most promising solutions to improve fuel efficiency towards achieving the reduction in carbon dioxide emissions. Fibre metal laminate is one of the lightweight material that inherits advantages of metal and fibre reinforced composite. Therefore, the drive of this study is to determine the effect of water absorption on tensile properties, thickness swelling and forming analysis of the natural fibre metal laminate. Fabrication of natural fibre metal laminate consists of two layers of kenaf woven fabric in polypropylene matrix and aluminium 5052-O as the skin. The results show that the natural fibre metal laminate absorbs 0.67% water and has 0.91% thickness swelling. The water content has minimal effect on the tensile properties of the natural fibre metal laminate. While for the forming analysis, the natural fibre metal laminate has higher formability compared to an aluminium sheet and has a higher potential to be formed into complex shape.